Penerapan Penilaian Klinis dalam Pelayanan Keperawatan di Instalasi Gawat Darurat : Application of Clinical Assessment in Nursing Services at the Emergency Department - Siti Nurlaelah; Yovitasari; Suleli Rekso; Arcellia Farosyah Putri (NERS Jurnal Keperawatan, 2024)
The ability of nurses in clinical judgments in emergency departments is really important. One reason is that the judgments can affect response time and patients’ condition. However, the ability to conduct such judgments among nurses varies. Therefore, continuously improving nurses' ability in clinical judgments is important. This article is a discussion conceptual-application paper. The aim of this article was to explain the concept of clinical judgment based on the NCSBN Clinical Judgement Measurement Model (NCJMM) and its implementation in the emergency department. The model consists of six cognitive processes: (1) recognize cues, (2) analyze cues, (3) prioritize hypotheses, (4) generate solutions, (5) take action, and (6) evaluate outcomes. The NCJMM model can be used to improve nurses’ ability in clinical judgments in emergency settings and others.